2000
DOI: 10.1037/0012-1649.36.3.394
|View full text |Cite
|
Sign up to set email alerts
|

Where's the ball? Two- and three-year-olds reason about unseen events.

Abstract: Children 2, 2 1/2, and 3 years of age engaged in a search task in which they opened 1 of 4 doors in an occluder to retrieve a ball that had been rolled behind the occluder. The correct door was determined by a partially visible wall placed behind the occluder that stopped the motion of the unseen ball. Only the oldest group of children was able to reliably choose the correct door. All children were able to retrieve a toy that had been hidden in the same apparatus if the toy was hidden from the front by opening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
253
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(278 citation statements)
references
References 21 publications
20
253
5
Order By: Relevance
“…Similarly, even though the existence and location of an invisible object can guide 14-month-olds' search after a significant delay, we do not think this dictates that all attributes of the object are available to the infant while the object is still occluded. For example, it has been reported that it is not until 2.5 to 3 years of age that children use the solidity of a hidden object blocking the path of a rolling ball to guide search (Berthier et al, 2000;Hood, Carey, & Prasada, 2000;Hood, Cole-Davies, & Dias, 2003). For further analysis of related developmental changes see Meltzoff and Moore (1998). enable assessment of visual behavior in very young infants.…”
Section: Object Permanencementioning
confidence: 99%
“…Similarly, even though the existence and location of an invisible object can guide 14-month-olds' search after a significant delay, we do not think this dictates that all attributes of the object are available to the infant while the object is still occluded. For example, it has been reported that it is not until 2.5 to 3 years of age that children use the solidity of a hidden object blocking the path of a rolling ball to guide search (Berthier et al, 2000;Hood, Carey, & Prasada, 2000;Hood, Cole-Davies, & Dias, 2003). For further analysis of related developmental changes see Meltzoff and Moore (1998). enable assessment of visual behavior in very young infants.…”
Section: Object Permanencementioning
confidence: 99%
“…Initially both Bruce Hood and we saw the toddlers' failure to search correctly as disagreeing with the infant data (see discussions in Berthier et al, 2000;Hood et al, 2000). At the same time both sets of authors independently suggested that task differences might explain the success of infants and the failure of toddlers to recognize the importance of physical solidity.…”
mentioning
confidence: 99%
“…Mash et al (2003) gave 2-year-olds full visual access to the ball's movement by first rolling the ball so that it came to rest against the wall before lowering the screen. When the screen was lowered to conceal ramp and ball, the top of the wall showed above the screen, serving as a continual reminder of the ball's location as in the original study (Berthier et al, 2000). Seeing where the ball stopped actually benefited the children very little.…”
mentioning
confidence: 99%
See 2 more Smart Citations